Local manganese chloride treatment accelerates fracture healing in a rat model. Issue 1 (17th September 2014) - Hreha, Jeremy; Wey, Aaron; Cunningham, Catherine; Krell, Ethan S.; Brietbart, Eric A.; Paglia, David N.; Montemurro, Nicholas J.; Nguyen, Daniel A.; Lee, Yung‐Jae; Komlos, Daniel; Lim, Elisha; Benevenia, Joseph; et al.
ABSTRACT This study investigated the effects of local delivery of manganese chloride (MnCl2), an insulin‐mimetic compound, upon fracture healing using a rat femoral fracture model. Mechanical testing, histomorphometry, and immunohistochemistry were performed to assess early and late parameters of fracture healing. At 4 weeks post‐fracture, maximum torque to failure was 70% higher (P < 0.05) and maximum torsional rigidity increased 133% (P < 0.05) in animals treated with 0.125 mg/kg MnCl2 compared to saline controls. Histological analysis of the fracture callus revealed percent new mineralized tissue was 17% higher (P < 0.05) at day 10. Immunohistochemical analysis of the 0.125 mg/kg MnCl2 treated group, compared to saline controls, showed a 379% increase in the density of VEGF‐C+ cells. In addition, compared to saline controls, the 0.125 mg/kg MnCl2 treated group showed a 233% and 150% increase in blood vessel density in the subperiosteal region at day 10 post‐fracture as assessed by detection of PECAM and smooth muscle α actin, respectively. The results suggest that local MnCl2 treatment accelerates fracture healing by increasing mechanical parameters via a potential mechanism of amplified early angiogenesis leading to increased osteogenesis. Therefore, local administration of MnCl2 is a potential therapeutic adjunct for fracture healing. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:122–130, 2015.